Analysis of Strategy Positioning, Segmenting, Institutional Image and Service Quality on Service Purchasing Decisions - Yekti Winarsih; Wiwiek Harwiki (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
This study aims to identify the influence of positioning, segmenting, institutional image and service quality strategies on service purchase decisions. The population in this study were all the guardians of Muhammadiyah 18 Surabaya elementary school students, consists of 537 student’s guardians. The sampling technique is cluster random sampling, then obtained 100 guardians of students to be asked to fill out the research questionnaire. The analytical method used to answer the hypothesis in this study is multiple regression analysis. The results of this study indicate that positioning, segmenting, and institution image do not affect service purchasing decisions, while the quality of service influences the purchasing decisions of education services at SD Muhammadiyah 18 Surabaya. The ineffectiveness of positioning, segmenting, and agency image strategies may be due to the inability of the school to determine and implement the strategy. Another possibility is that the influence of the strategy is mediated by the interest of students attending Muhammadiyah Elementary School. Future studies are expected to be able to use intervening variables or other measurements to identify the direct and indirect effects of positioning, segmenting, institutional image, service quality and student interest in service purchasing decisions.